Spatial distribution and risk factors for Toxoplasma gondii seropositivity in cattle slaughtered for human consumption in Rondônia, North region, Brazil - de Souza, Juliana Bianca Rocha; Soares, Vando Edésio; Maia, Maerle Oliveira; Pereira, Cleidiane Magalhães; Ferraudo, Antônio Sergio [UNESP]; Cruz, Breno Cayeiro; Pires Teixeira, Weslen Fabrício; Felippelli, Gustavo; Maciel, Willian Giquelin; Gonçalves, Walter Antonio; da Costa, Alvimar José; Zanetti Lopes, Welber Daniel (My University, 2016)
The present study aimed to evaluate Toxoplasma gondii seroprevalence in cattle slaughtered for human consumption from rural properties in the state of Rondônia, North region, Brazil; the seroprevalence was determined using indirect immunofluorescence assays (IFATs). Additionally, spatial distribution and risk factors associated with toxoplasmosis were also analyzed. Of the 1000 cattle serum samples examined, 53 (5.3%) were determined to be seropositive for T. gondii with antibody titers (IgG) ≥64. In regard to results of the studied risk factors (presence of cats, cats with free access to cattle, breeding system, animal's gender, consumption of raw milk by humans on the property and cattle abortion in the last 12 months) and the odds ratio (OR) of each of these factors influencing cattle to acquire toxoplasmosis, only animals raised on a feeder/stocker/backgrounder system presented a higher probability of being seropositive for T. gondii (OR ≥ 1, P = 0.04) than cattle raised only in a feeder/stocker system. There was no association between the occurrence of reproductive problems and T. gondii seropositivity. Based on results obtained in the Brazilian state of Rondônia, it could be concluded that the presence of cats and their contact with cattle on each property, cattle breeding purpose and cattle abortion in the last 12 months were not considered risk factors for T. gondii infection in cattle. Considering that the presence of T. gondii was detected in animals slaughtered in the state of Rondônia, consuming raw or undercooked meat from seropositive cattle should be considered a route of transmission of T. gondii to humans. However, the prevalence of toxoplasmosis diagnosed in cattle from this state (5.30%) is lower than the prevalence of toxoplasmosis observed in South, Southeast and Center-West regions of Brazil, which may vary between 48.5% and 71.0%. The low prevalence of toxoplasmosis in cattle is highlighted in Rondônia, which is the sixth largest state for cattle slaughtering in Brazil and is responsible for producing 20% of all cattle meat exported by Brazil.
Keywords: Brazil; Indirect immunofluorescence assay (IFAT); Rondônia; Serology; Toxoplasma gondii